Physicians’ Perception and Practice of Prescribing Vitamin B Combination versus Antiepileptic Drugs for Diabetic Neuropathy: Content Validity, Reliability and Pilot Study - Essa, Narmin; Aladul, Mohammed (Iraqi Journal of Pharmaceutical Sciences, 2023)
Background: Diabetic neuropathy (DN) is the most common complication of diabetes mellitus causing increased morbidity and mortality. Although international guidelines did not include vitamins and dietary supplements in any line of management, these agents were prescribed by a significant number of physicians either as preventive or treatment of DN. This study aimed to develop a validated questionnaire that examines the physicians’ perception and practice towards prescribing vitamins or dietary supplements for DN treatment. Method: The questionnaire was developed upon literature review via PubMed, Medline, Web of Science, Scopus, and Google Scholar. The questionnaire was revised upon experts’ views and opinions. The constructed questionnaire was validated by the means of content validity and internal consistency. Finally, the developed questionnaire was piloted in a small representative sample of the original future aimed research target population, to test its applicability and feasibility. Results: A total of 19 items questionnaire were developed in two domains (perception and practice). Content validity analysis results met a satisfactory level, in which the S-CVI/UA value was 0.84 and 0.89 for clarity and relevance respectively. The questionnaire also showed good reliability, in which the Cronbach’s alphas was 0.824. Conclusion: This study showed the ability to construct a questionnaire with good levels of content validity and reliability that can cover different aspects of the current state of perception and practice among physicians regarding the management of DN.